Choice of interest rate term structure models for assets and liability management - Zhenke Guan; Bing Gan; Aisha Khan; Ser-huang Poon (The University of Manchester, Manchester Business School, 2008)
This paper compares the pricing and hedging performance of the LMM model against two spot-rate models, namely Hull-White and Black-Karasinski, and the more recent Swap Market Model from an Asset-Liability-Management (ALM) perspective. In contrast to previous studies in the literature, our emphasis here is on ALM and we use hedging performance on Bermudan swaptions to proxy risk management outcome of long-term mortgage loans. Our tests involve calibrating the four interest rate models to European swaption prices for EURO and USD over the period February 2005 to September 2007. The calibrated models are then used to price and hedge a constant 11-year Bermudan swaption portfolio using a series of interest rate swaps and a 1-year holding-revision period. Our empirical results show that, the calibrated parameters of all four models are stable and their pricing errors are small and comparable. No single model dominates in the pricing exercise. The hedging performance of all four models is similar for the Euro market. For the USD market, the short rate models perform marginally better than SMM and LMM. The HW model is marginally better than BK model in terms of model parameter stability and smaller pricing and hedging errors.
Keywords: 330; asset-liability management; Hull-White; Black-Karasinski; libor market model; swap market model; Bermudan swaptions; Währungsmanagement; Hedging; Währungsswap; Dynamisches Modell; Monetäre Wechselkurstheorie